2014
DOI: 10.1177/0741713614541461
|View full text |Cite
|
Sign up to set email alerts
|

Math Anxiety, Math Self-Concept, and Math Self-Efficacy in Adult Learners Compared to Traditional Undergraduate Students

Abstract: Adult learners comprise a significant portion of current undergraduate populations, and projections indicate steady or growing numbers of adult learners in the future. Previous research has suggested that adult learners possess lower self-confidence than and face barriers not experienced by traditional undergraduate students. These constructs have not been explored specifically within mathematics, however, which was the purpose of the current study. Using data collected from 226 undergraduate students (60 trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 63 publications
(93 reference statements)
3
85
0
7
Order By: Relevance
“…Among college samples, self-confidence in ability is argued to affect some types of students differently than others. Jameson and Fusco (2014) show adult learners have lower levels of mathematics self-efficacy than traditional students. Gender and racial/ethnic differences in self-confidence in mathematics ability, student attitudes, and intentions toward mathematics education have also been highlighted in academic research.…”
Section: Discussionmentioning
confidence: 99%
“…Among college samples, self-confidence in ability is argued to affect some types of students differently than others. Jameson and Fusco (2014) show adult learners have lower levels of mathematics self-efficacy than traditional students. Gender and racial/ethnic differences in self-confidence in mathematics ability, student attitudes, and intentions toward mathematics education have also been highlighted in academic research.…”
Section: Discussionmentioning
confidence: 99%
“…The 'Motivated Strategy for Learning Questionnaire' was used by Justice and Dornan (2001) to explore metacognitive differences between traditional and non-traditional students and focuses on factors like test anxiety, self-efficacy and self-regulation. Anxiety in relation to mathematics courses was assessed by Jameson and Fusco (2014) Inventory' which consists of 21 anxiety items and which has, according to previous research, a strong internal consistency. Self-efficacy has also been the main variable in research conducted by Van Rhijn and Lero (2014) with Canadian student parents.…”
Section: Psychometric Scalesmentioning
confidence: 99%
“…The results showed that around 30% of students reported feeling helpless or nervous when faced with math problems, and negative feelings towards math are also associated with lower school performance. Special attention has been paid to MA and its impact on mathematical learning: an ever-growing body of research has recognised that anxiety states and worry experienced during math classes or related activities are significant factors with a negative influence on math learning and basic numerical abilities in both adults (Bursal & Paznokas, 2006;Jameson & Fusco, 2014;Pozehl, 1996;Maloney & Beilock, 2012;McMullan, Jones, & Lea, 2010;Swars, Daane, & Giesen, 2006) and children (Hill et al, 2016;Wu, Barth, Amin, Malcarne, & Menon, 2012). MA thus seems to have serious consequences, not only in the short term (on math performance at school), but also in the long term, adversely influencing an individual's choice of career, type of occupation and professional growth in adulthood (Ashcraft & Ridley, 2005;Beasley, Long, & Natali, 2001;Chipman, Krantz, & Silver, 1992;Hembree, 1990;Ho et al, 2000).…”
Section: Thinking and Reasoningmentioning
confidence: 99%